Case Report: Pediatric alloplastic nose reconstruction with a 3D printed patient specific titanium implant - Ureel, Matthias; Dadjam, Daniel; Dhooghe, Nicolas; De Jong, Maarten; Coopman, Renaat (Frontiers in Surgery, 2024)
An 11-year-old girl presented at the emergency service with a nasal defect caused by a dog bite in the midface. Autologous nose reconstruction in the pediatric population is challenging due to donor site morbidity and remaining facial growth. Temporary prosthetic treatment is difficult to accept due to problems with retention. We present an innovative solution using a 3D printed patient specific titanium implant for support of a nasal prosthesis. With preoperative 3-dimensional planning, the implant can be designed to find fixation in the areas with the best bone quality, avoid potential damage to tooth buds and dental roots and avoid interference to soft tissues such as the nasal septum. Clear communication between the prosthetist, surgeon and medical engineer is crucial for treatment success. The impact of facial growth is still unclear and will have to be assessed.